Respostas
respondido por:
58
An=A1+(n-1).r
6=-3+(n-1).5
6=-3+5n-5
5n-8=6
5n=6+8
5n=14
n=14/5
6=-3+(n-1).5
6=-3+5n-5
5n-8=6
5n=6+8
5n=14
n=14/5
respondido por:
184
a₁ = - 3
n = 6
r = 5
a₆ = a₁ + (n - 1) * r
a₆ = - 3 + (6 - 1) * 5
a₆ = - 3 + 5 * 5
a₆ = - 3 + 25
a₆ = 22
PA (-3, 2, 7, 12, 17, 22)
Espero ter ajudado. Valeu!
n = 6
r = 5
a₆ = a₁ + (n - 1) * r
a₆ = - 3 + (6 - 1) * 5
a₆ = - 3 + 5 * 5
a₆ = - 3 + 25
a₆ = 22
PA (-3, 2, 7, 12, 17, 22)
Espero ter ajudado. Valeu!
Anônimo:
Obrigado por marcar minha resposta como a melhor. Valeu!
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás